Impact of porous fins on thermal convection in a differentially-heated cubical chamber - Le, Xuan Hoang Khoa; Öztop, Hakan Fehmi; Sheremet, Mikhail A. (Springer, 2025)
Thermal transport enhancement can be achieved using various techniques. Nowadays, one of the very interesting and useful passive approaches is to use the porous fins for the classical heat transfer fluids. The objective of this research is to numerically investigate the impact of porous fins on convective heat transfer performance inside a differentially-heated cubical cavity. An effect of different characteristics including Rayleigh number (10(4) <= Ra <= 10(6)), dimensionless fin length (0.2 <= l <= 0.8), dimensionless fin position (0.2 <= d <= 0.6), fin number (1 <= N <= 3), and porosity (0.8 <= epsilon <= 0.99) on liquid circulation and heat transfer performance has been studied. Mathematical model formulated using the Oberbeck-Boussinesq equations combined with the Brinkman-extended Darcy approach for the porous fins have been closed employing the additional restrictions. Governing equations have been worked out using the finite-difference technique and hybrid non-primitive variables including velocity and vorticity vectors. The results indicate that using porous fins enhances thermal energy transport by up to 50% compared to finless cavities. Moreover, a single porous fin placed close to the bottom surface (d = 0.2) with a relative length of l = 0.6 is considered the best configuration for most cases for cubical cavities. It has been also found that porosity ranging from 0.8 to 0.99 has minor impact on heat transfer performance.
Keywords: Natural convection; Heat transfer; Fins; Porous media; Mathematical modeling